2001
DOI: 10.2527/2001.791254x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine on nitrogen retention and blood metabolites of growing steers and performance of finishing steers.

Abstract: Two experiments were conducted to evaluate L-carnitine supplementation to cattle fed grain-based diets. In Exp. 1, seven Angus-cross steers (216 kg) were used in a 7 x 4 incomplete Latin square experiment to evaluate the effects of supplemental L-carnitine on N balance and blood metabolites. Steers were fed a corn-based diet (17.5% CP) at 2.5% of BW. Treatments were 0, 0.25, 0.5, 1.0, 1.5, 2.0, and 3.0 g/d of supplemental carnitine. The 18-d periods included 13 d for adaptation and 5 d for collection of feces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 13 publications
4
32
1
Order By: Relevance
“…Given the fact that dietary RPLC above 0.25 g/day did not increase plasma LC concentrations and that plasma concentrations from both experiments resulted in similar plasma LC concentrations even when significantly different amounts of LC were consumed, three possibilities exist: either the RPLC was not absorbed from the intestine, the RPLC was absorbed but was rapidly excreted, or was rapidly metabolised upon absorption. Greenwood et al. (2001) reported that, in calves, urinary excretion of LC was elevated as the treatment increased from 0.25 to 3.00 g/day.…”
Section: Resultsmentioning
confidence: 98%
“…Given the fact that dietary RPLC above 0.25 g/day did not increase plasma LC concentrations and that plasma concentrations from both experiments resulted in similar plasma LC concentrations even when significantly different amounts of LC were consumed, three possibilities exist: either the RPLC was not absorbed from the intestine, the RPLC was absorbed but was rapidly excreted, or was rapidly metabolised upon absorption. Greenwood et al. (2001) reported that, in calves, urinary excretion of LC was elevated as the treatment increased from 0.25 to 3.00 g/day.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, fecal N for all diet treatments is assumed to be 50% of total N discharge in the control diet (which had adequate N supply) although values of 26 to 66% have been reported in the literature (Bierman et al, 1999; Cole et al, 2003; Hoffman et al, 2001; Kohn et al, 2005). All diets supplied adequate protein for cattle growth, so any excess N intake above the control diet is known to be excreted in the urine (Archibeque et al, 2002; Bolan et al, 2004; Greenwood et al, 2001; Wessels and Titgemeyer, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Concentration of IGF-I in serum samples was determined with use of a commercial two-site immunoradiometric assay (Diagnostic Systems Laboratories, Inc., Webster, TX) previously validated for bovine serum [23]. Serum samples (50 l) were acid-ethanol extracted per the manufacturer's instructions and run in duplicate in a single assay.…”
Section: Immunoassaysmentioning
confidence: 99%